CEREBRAL NEURODYNAMICS IN PATIENTS WITH STROKE AND UPPER LIMB INJURIES DURING REHABILITATION - B. I. Vakhitov; I. S. Raginov; I. Kh. Vakhitov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
The problem of rehabilitation therapy after ischemic strokes is one of the most relevant in current neurology [4, 7]. Neurophysiological research is currently leading in the evaluation and control of brain plasticity. Approximately 80% of all injuries are the injuries to the musculoskeletal system; almost half of them are upper limb traumas. Treatment efficacy depends on the quality of first aid. Conservative treatment methods are effective in 13%–60% of patients, whereas with surgical methods, the efficacy is between 10% and 70%. Moreover, patients with radius fractures usually lose their ability to work for 6 to 8 months; 10% of them have to change their profession after it; 6% to 17% of patients become disabled. Rehabilitation of such patients should include dynamic electroencephalographic (EEG) monitoring, since the information about the functional state of cerebral structures is necessary for organizing an effective rehabilitation program, predicting and assessing treatment outcomes.We have examined 26 patients with cerebral stroke (14 men and 12 women aged 42–65 years) in the early stages with the leading neurological syndrome manifesting as spastic hemiparesis and 27 patients with extension fractures of the distal radial physis (after manual reposition and plaster splint removal) at different stages of their rehabilitation with a week interval.We found that changes in brain electric activity (from similar leads of the contralateral hemisphere) were more significant in patients with acute stroke, which can be associated with specific changes in the cerebral rhythms after stroke, since deep location of the alteration focus results in more diffused EEG symptoms due to conducting paths. Positive dynamics in the reduction of slow-wave activity above the affected area in the late rehabilitation period was more pronounced in patients who performed dynamic and static exercises. Normalization of electrogenesis was more effective in patients performing static exercises than in those performing dynamic exercises.